On the international cooperation of North-West Russia in the field of innovations in the Baltic - Baranova, Yulia V. (Baltic Region, 2013)
This article focuses on the cooperation between the constituent entities of the Northwestern Federal District of the Russian Federation and the Baltic countries (Finland, Estonia, and Norway) in the field of innovations at national and regional levels, as well as at the level of corporate cooperation. The author reviews successful implementation of innovation projects within cross-border and transnational cooperation programmes. The most significant projects focus on the development of information and communications technologies in healthcare, the development of networks uniting innovation centres in the Baltic Sea region, and the transnational network of business incubators in the Baltic Sea region. The author identifies promising areas of cooperation between North-West Russia, Finland, Norway, and Estonia in the field of innovations, including telecommunications, information and, space; biological, environmental and nanotechnologies; software, medicine, education, culture, energy efficiency and ecological construction, as well as the development of creative industries. The article pays attention to large-scale national projects, such as "St. Petersburg Corridor - Two Model Open Innovation Platform" and "Partnership in commercialization of Russian innovations".